Characterization of Growth and Atresia of Buffalo Ovarian Follicles by Follicular Fluid Hormonal Levels and Transcripts Expression Studies - Patil, Anand; Nazar, Syedbasha; Selvaraju, Sellappan; Chandrasekaramurthy, Virupakshaiah; Ravindra, Janivara P. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The influence of CL on follicular development and the changes in the follicular fluid composition leading to attainment of follicular dominance and ovulation has not been intensively studied in the buffalo. In the present study, the buffalo ovarian follicular fluids were collected from live animals by transvaginal ultrasound guided follicular aspiration. Based on the size of the follicles and stage of the estrous cycle, follicles were classified into 3–5 mm (small), 5–8 mm (medium) and >8 mm (large ovulatory and non-ovulatory). The follicles were classified into healthy and atretic follicles based on nuclear quality as assessed by histological staining. The stage and health status of the follicles were confirmed by the serum progesterone and follicular fluid hormonal concentration. Hormone concentration (serum and follicular fluid) and HDL cholesterol were estimated in follicular fluids, and expression of LH and 3β hydroxysteroid dehydrogenase (3β HSD) receptors was studied in granulosa cells of different sizes. The study revealed that the presence of CL influences the growth of the follicles of all stages. Significantly high follicular fluid progesterone in the ovulatory follicles indicated that the luteinization of granulosa cells starts even before ovulation of the dominant follicle. The medium-sized follicles with high estradiol concentration may attain dominance, whereas the follicle with high progesterone concentration may undergo atresia. A significantly low HDL cholesterol level in healthy follicles indicates effective steroidogenesis as evidenced by the higher expression of LH and 3β-HSD receptors in the granulosa cells.